Teatralitet og performativitet: to sider af samme sag – næsten? - Kjølner, Torunn (Peripeti, 2007)
In her introduction to theatricality and performativity, Torunn Kjølner casts light on a similarity in the development of both concepts. Initially, she argues, both concepts were connected to a relatively limited field of knowledge (Theatre Arts), but has presently become central terms in the vocabulary of a large variety of scientific disciplines. Consequently, both »theatrical« and »performative« are widely used both in everyday language, in different art cultures, and in the complex theoretical constructions of disciplines such as sociology and aesthetics.